Isolation and structural elucidation by 2D NMR of planteose, a major oligosaccharide in the mucilage of chia (Salvia hispanica L.) seeds. (1st November 2017) - Xing, Xiaohui; Hsieh, Yves S.Y.; Yap, Kuok; Ang, Main E.; Lahnstein, Jelle; Tucker, Matthew R.; Burton, Rachel A.; Bulone, Vincent
Highlights: The unusual oligosaccharide planteose was isolated from chia seed mucilage. A simple, low-cost and robust solid-phase separation method was used to isolate planteose. Excellent yields of pure planteose were obtained for structural characterization. The complete assignment of a series of 2D NMR spectra was achieved on planteose. The amount of pure planteose obtained allows nutritional and functional studies. Abstract: An oligosaccharide was isolated in high purity and excellent yield from the water-extractable mucilage of chia ( Salvia hispanica L.) seeds using an optimized solid-phase extraction method. LC–MS analysis showed that the compound presents a molecular mass of 504 Da and trifluoroacetic acid hydrolysis revealed that it consists of galactose, glucose and fructose. Glycosidic linkage analysis showed that the oligosaccharide contains two non-reducing ends corresponding to terminal glucopyranose and terminal galactopyranose, respectively. The oligosaccharide was identified as planteose by the complete assignment of a series of 2D NMR spectra (COSY, TOCSY, ROESY, HSQC, and HMBC). The significance of the presence of planteose in chia seeds is discussed in the context of nutrition and food applications.